Transformation of the Young Generation of Kemtuk Gresi: The Key to Success in Building a Career in the Digital Era - Mikhael Udam; Yansen Alberth Reba; Yulius Mataputun; Habel Saud; Listini Bestina Kamarea; Sally Putri Karisma (LP4MK STKIP PGRI Lubuklinggau, 2024)
This community service activity aims to empower the youth in Kemtuk Gresi District to be ready to embark on digital careers, where digital skills are highly needed in the job market. This program is designed to equip participants with a strategic understanding of digital career opportunities as well as technical skills and non-technical skills such as effective communication and professional networking. (networking). Through interactive seminars and workshops, participants learn the use of digital technology, content management, and personal branding strategies. Participatory methods and group discussions help participants develop skills that align with the current needs of the job market. The results of the activities show a significant increase in participants' understanding of technology as a career development tool and the enhancement of technical skills that support their readiness in the digital job market. In addition to basic skills, participants were also introduced to sustainable career planning strategies in the digital era. This program successfully guided the youth of Kemtuk Gresi to become more adaptive and ready to face global challenges with skills and knowledge that enable them to pioneer digital careers.